2018
DOI: 10.3390/economies6020031
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate and Oil Price Interactions in Selected CEE Countries

Abstract: This paper reports a study on the causal dynamics between spot oil price, exchange rates, and stock prices in Poland, the Czech Republic, Hungary, Romania, and Serbia. The results are compared with a benchmark analysis in which U.S. monthly data are used, and time periods are selected according to the flexibility of exchange rate regimes in each country. A period between 2000 and 2015 is analyzed. The methodology is based on the Granger causality test, and the non-linear Diks-Panchenko test, while the causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Moreover, it should be noted that most of previous investigations have been restricted to linear framework, ignoring the possible nonlinear behaviors, which may be caused by asymmetry, persistence, or structural breaks [21]. The nonlinear Granger causality tests were applied to detect the relationships between crude oil price and exchange rates by [8,[22][23][24]63]. The results of these studies were also mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be noted that most of previous investigations have been restricted to linear framework, ignoring the possible nonlinear behaviors, which may be caused by asymmetry, persistence, or structural breaks [21]. The nonlinear Granger causality tests were applied to detect the relationships between crude oil price and exchange rates by [8,[22][23][24]63]. The results of these studies were also mixed.…”
Section: Discussionmentioning
confidence: 99%
“…[10]). The nonlinear analysis of the relationships between crude oil prices and exchange rates has been performed much more rarely than the linear one, but the obtained results show that it can give a better insight into the mechanism of the investigated dependencies (e.g., [8,[20][21][22][23][24]). It has been argued that the nonlinear causality behavior between oil prices and exchange rates can be explained by asymmetric responses of economic activity to oil price shocks [25][26][27], the negative effects of oil price uncertainty on economic activity [28], structural breaks, persistence and discontinuity in the adjustment (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Morema and Bonga-Bonga (2018) showed returns in the industrial sector are more affected by oil prices. Based on these findings, the following hypotheses suggested: H1: The spillover effect of return and volatility of oil and stock price is met H2: The spillover effect of return and volatility of gold and exchange rate is met H3: The spillover effect of return and volatility of oil and gold is met Drachal (2018) found that oil price has a negative impact on exchange rates. Similarly, Arfaoui and Rejeb (2017) revealed that gold and USD positively impact the oil price.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…They have been correlated with each other and the global business cycle outlook (Mikhaylov, 2018). According to Drachal (2018), a specific change in the stock index price due to changes in the exchange rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation